THE ESSENCE OF THE ENGLISH LANGUAGE AND ITS ROLE IN MODERN SOCIETY - Tojiyeva Marxabo Akbarovna, (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Abstract This  article  analyzes  the  role  of  the  English  language  in  the  modern  world, emphasizing  its  essence  not  merely  as  a  tool  for  communication,  but  as  the  main driving force of global integration, science, technology, and business. It highlights the historical development stages of the language and the reasons for its rise to the status of a "lingua franca" (universal language of communication). Furthermore, the positive impact of learning English on personal and professional development is demonstrated.